Impact of new state border on development of ethno-cultural space (illustrated by Orenburg-Kazakhstan borderline) - Tatiana I. Gerasimenko (Наука. Инновации. Технологии, 2022)
Global and regional development are two sides of the same process. In the era of globalization regional components play an important role in the process of development. Displacement and blurring of borders are global trends at the present time. Trans-border interaction results in the formation of trans-border regions as parts of multilayer system. Ethno-cultural space is one of the most important subsystems of this system. Special attention is paid to the modern stage of development, the main factor which became the state border. This article uses the results of the field research of the author